DINAMIKA STRUKTUR PENDAPATAN ASLI DAERAH (PAD) KOTA MADIUN - Henry Windrianto Darmoko Darmoko (Universitas Merdeka Madiun, 2025)
The purpose of this research is to analyze the structure of Madiun City's Regional Original Revenue (PAD) from 2022 to 2024. The research question is, are the fluctuations in Madiun City's PAD from 2022 to 2024 caused by the dynamics of existing PAD sources? This research uses a quantitative descriptive analysis approach. The type of data used is secondary data. The data source in this study is the Madiun City Regional Revenue Agency. The data used is the report on the realization of Madiun City's regional revenue receipts for 2022-2024, consisting of regional taxes, regional levies, the results of separated wealth management, and other legitimate PAD. The data analysis technique used is mathematical techniques, including data grouping and data calculations. The aim is to ensure that the data can be compared and analyzed carefully, to serve as a basis for making accurate conclusions. The results of the analysis above have provided evidence that the dynamics of Madiun City's PAD acquisition from 2022 to 2024 are caused by the dynamics of the PAD structure in Madiun City from 2022 to 2024.